2020
DOI: 10.30659/e.5.2.240-250
|View full text |Cite
|
Sign up to set email alerts
|

Instagram post: Writing caption through process approach in developing writing skill

Abstract: Instagram has some features for supporting English learning process. Posting a picture and adding a caption could be a way for developing writing skill. Instagram users are allowed to write caption through process approach that would guide them to make a good writing. This study aims to find out the effect of Instagram caption through process approach on students� writing skill in recount text. Quasi-experimental design was implemented to the two classes of Multimedia students at one of Indonesian vocational h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…That is the importance of choosing a type of language style in writing using social media, especially Instagram, appropriate to the context and circumstances. In the studies (Avivi, 2020) and (Klimova, 2020) explain that writing in a figurative language style is a systematic space for developing the concept of a writing style and can show the reader's knowledge about the idea of the type of target language style. That relationship is what provides clarity in a sentence.…”
Section: Discussionmentioning
confidence: 99%
“…That is the importance of choosing a type of language style in writing using social media, especially Instagram, appropriate to the context and circumstances. In the studies (Avivi, 2020) and (Klimova, 2020) explain that writing in a figurative language style is a systematic space for developing the concept of a writing style and can show the reader's knowledge about the idea of the type of target language style. That relationship is what provides clarity in a sentence.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the approach has a favourable influence on developing English writing skills since it encompasses all stages of the writing process, such as planning, drafting, editing, and final version (e.g. Avivi & Megawati, 2020;Kasi & Jayapalan, 2021). Moreover, Kadmiry (2021) stated that students who received instruction based on the process approach demonstrated superior performance compared to those taught using a product-based approach.…”
Section: Effective Instructional Practices To Teach Writing Skillsmentioning
confidence: 99%
“…It helps provide an ideal environment for students to learn. Research has shown that Instagram features can benefit English teachers and students and be promoted as an engaging teaching technique for writing skills [4]. Instagram itself is a mobile her application that allows users to take photos and images, apply various manipulation tools to change their appearance and images, and instantly share them with friends on various social her networking sites [5].…”
Section: Introductionmentioning
confidence: 99%